Wszczep ślimakowy dla pacjentów z głuchotą postlingwalną – szansa na poprawę jakości życia - Magierska-Krzysztoń, Magdalena; Olempska-Wysocka, Magdalena (Wydawnictwo Naukowe UAM, 2018)
Permanent hearing damage, which was diagnosed in the postlingling period - prevents “normal” life. Adult, mature people who until now had certain social roles and activities, suddenly experienced the phenomenon of exclusion as a result of hearing loss, which leads in many cases to personal dramas. The aim of the research was to determine the possibility of improving the quality of life of patients with postlingual deafness after implanting the cochlear implant. The study involved 96 patients aged 30-75 years, postlingally deaf, equipped with a cochlear implant. The study used the CES-D questionnaire, the PANAS-PL questionnaire and the diagnostic survey method (questionnaire survey). The results of the study show that in the majority of patients after implantation, there was a subjectively evaluated improvement associated with activity in various spheres of life. The use of the cochlear implant in post-lethal hearing impaired patients allowed to achieve satisfactory auditory functioning, which contributed to the improvement of the quality of life.
A Cochlear Implant for Patients with Postlingual Deafness – a Chance to Improve the Quality of Life
Keywords: quality of live; cochlear implant; postlingual deafness